The Connection between Low Birth Weight and Knowledge Level Regarding the Incidence of Stunted in Kedunglumpang Vilangge and Dukuh Mojo Village - Fadayeen Khoirun Nisa'; Woro Setia Ningtyas; Irwanto (PROFESSIONAL HEALTH JOURNAL, 2025)
Stunted It refers to a situation where a child's height or body length is below -2 standard deviations (SD) referencing the WHO growth and development standards, which arises from lack of inadequate nutritional intake. The main focus of this investigation is to investigate the research investigates the association between knowledge and prevelance rates of stunted in Kedunglumpang Village and Dukuh Mojo Village. This research employs a quantitative approach using an employing a case-control methodology. The study subject consists of children aged 2 – 5 years who lived in Kedunglumpang Village and Dukuh Mojo Village. This study involved 100 samples with 53 case samples and 47 control samples obtained using consecutive sampling the method employed utilized a questionnaire as the primary instrument from previous research. The methodological analysis method the statistical significance was assessed using chi-square. The findings indicate the statistical test yielded a p-value of 0.028, which less than α (0.05), indicating a statistically significant result, indicating a significant association between low birth weight and the risk of stunted. Similarly, the results of the quantitative analysis test for the level of knowledge showed a p-value of 0.009, meaning also below the threshold of α (0.05), indicating a significant correlational analysis knowledge level and the incidence of stunted. The odds ratio (OR) for the level of knowledge, Results indicate statistical significance at the 95% confidence level, is 4.141. This suggests that the case the group is 4.141 results suggest an increased risk stunted relative to the control group